2021
DOI: 10.1083/jcb.202002114
|View full text |Cite
|
Sign up to set email alerts
|

Rac1-PAK1 regulation of Rab11 cycling promotes junction destabilization

Abstract: Rac1 GTPase is hyperactivated in tumors and contributes to malignancy. Rac1 disruption of junctions requires its effector PAK1, but the precise mechanisms are unknown. Here, we show that E-cadherin is internalized via micropinocytosis in a PAK1–dependent manner without catenin dissociation and degradation. In addition to internalization, PAK1 regulates E-cadherin transport by fine-tuning Rab small GTPase function. PAK1 phosphorylates a core Rab regulator, RabGDIβ, but not RabGDIα. Phosphorylated RabGDIβ prefer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 93 publications
(155 reference statements)
0
8
0
Order By: Relevance
“…The regulons driven by these TFs in R probably played important roles in tumorigenesis or progression in the Abi-sensitive samples. For example, we showed that knockdown of ETS family gene ELK3 suppressed the proliferation of Abi-sensitive prostate cancer cell lines and, more importantly, inhibited migration by suppressing the expression of genes related to focal adhesion and motility, including RAPGEF1 59 , ACTN4 60 , RAB11B 61 , MYO18A 62 , and PIK3CA 63 .…”
Section: Discussionmentioning
confidence: 99%
“…The regulons driven by these TFs in R probably played important roles in tumorigenesis or progression in the Abi-sensitive samples. For example, we showed that knockdown of ETS family gene ELK3 suppressed the proliferation of Abi-sensitive prostate cancer cell lines and, more importantly, inhibited migration by suppressing the expression of genes related to focal adhesion and motility, including RAPGEF1 59 , ACTN4 60 , RAB11B 61 , MYO18A 62 , and PIK3CA 63 .…”
Section: Discussionmentioning
confidence: 99%
“…We found that invasion of trastuzumab-sensitive cells is regulated by α V β 6 , HER2, RAB5 and RAB7A, and that activity of GDI2 constrains this invasive capacity. GDI2 is a relatively under-studied Rab GDPdissociation inhibitor; ostensibly a negative regulator of Rab function capable of extracting GDP-bound inactive Rabs from vesicular membranes and sequestering them in a cytosolic pool, before redelivery to acceptor endosomes 62,95 . Our data identify GDI2 as a key regulator of α V β 6 -mediated RAB5 activity and HER2 endocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…While needing further investigation, these observations may be indicative of disrupted RAB5/RAB7A conversion in trastuzumab resistant cells, due to dysregulated GDI2 activity. Recent work demonstrated that PAK-mediated phosphorylation of GDI2, downstream of Rac1 activation, increases affinity of GDI2 for RAB5 62 , so it is conceivable that Rho-family GTPase and Rab-family GTPase signals converge to co-ordinate α V β 6 -and RAB5-mediated HER2 trafficking. Moving forward, it will be important to investigate this intriguing hypothesis and determine whether GDI2 plays a key role in rab conversion to co-ordinate endolysosomal dynamics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is thought that Rab GDIs modulate Rab function and activity by extracting inactive GDP-bound Rabs from membranes, solubilising and chaperoning the hydrophobic prenylated GTPases in the cytosol, and mediating delivery to their cognate membranes, in preparation for the next cycle of activation (52,54,58,59). The full range of GDI2 targets is unknown, however GDI2 has been shown to associate with and modulate RAB5 (60)(61)(62). Therefore, we examined whether GDI2 regulates αVβ6-dependent HER2 trafficking and cell surface bioavailability.…”
Section: Gdi2 Regulates αVβ6-dependent Rab5 Activity and Cell Migrationmentioning
confidence: 99%